Azo dye (direct blue 14) decolorization by immobilized extracellular enzymes of Pleurotus species - Vishwakarma, S. K.; Singh, M. P.; Srivastava, A. K.; Pandey, V. K. (Cellular and Molecular Biology, 2012)
Four species of Pleurotus i.e., P. florida, P. ostreatus, P. citrinopileatus and P. eryngii were evaluated for laccase and MnP production in submerged condition. Among these P. ostreatus showed highest production of laccase and MnP. Twelve days old culture of P. ostreatus produced 1096 U/ml and 693.5 U/ml of the laccase and MnP, respectively. Crude extracts of enzymes from P. ostreatus were immobilized in Ca- alginate matrix and tested for decolorization activity of the azo dye (Direct blue; CI 23850) in aerobic and microaerophilic condition for 24h. Treatment of dye with the immobilized enzymes decolorized up to 99% in eighteen hour.